Jejak Keindiaan (Hindu-Buddha) dalam Kebudayaan Pakpak - Ery Soedewo (Balai Arkeologi Sumatera Utara, 2008)
AbstractPakpak as one of the ethnic group in North Sumatera, showed that its cultural heritage had been influenced by Indian culture. Indian culture added into Pakpak culture then enriched it. This addition didn’t change Pakpak’s identity.